Historical, Epistemological and Didactic Study of the Parabola - Aldana Bermúdez, Eliécer; López Mesa, Jorge Hernàn (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This study is part of a research conducted with freshmen systems engineering students at the University of Quindío in an analytic geometry course, in order to analyze how they get to comprehend and construct the concept of the parabola as cone at historical, epistemological, didactic and cognitive levels. The study is based on the theoretical framework of the didactical situations developed by Brousseau who considers the relations in the triad of knowledge, student and teacher, where commitments ensuring the analysis and comprehension of a concept are made. Thus, the teacher makes a transposition of theoretical concepts using Chevallard’s didactic engineering as the research method. To this end, several instruments were implemented such as: surveys, semi-structured interviews, video recordings and the support of IT environments backed up by the GeoGebra application. The results enable to conclude that a historical, pistemological and didactic study as well as the use of didactic teaching sequences ruled by IT environments, promote a progressive development of the students when understanding the concept of the parabola.